The impact of ecological civilization construction on the resilience of green technology innovation: evidence based on double dual machine learning - Li, Cunlin; Zhang, Shiyu; Yang, Baojun (Frontiers in Environmental Science, 2025)
Can the accelerated development of ecological civilization promote the sustainable development of green innovation?This paper investigates the effects of ecological civilization demonstration zones (ECDZs) on green innovation resilience. Based on a sample of 237 prefecture-level cities across 31 provinces in China from 2011 to 2021, our double dual machine learning and spatial difference-in-differences model indicates that ECDZs significantly enhance urban green innovation resilience. Our findings also reveal a spatial spillover effect of ECDZ—the development of ECDZs in one city significantly improves the resilience of green innovation in neighboring cities. The spatial spillover effect reaches its maximum in the fifth year. Our analysis of the underlying mechanisms suggests that ECDZs promote urban green innovation resilience through the advancement of digitalization, green consciousness, and new quality productivity. We also conduct an analysis of heterogeneity based on geographical locations and levels of policy support, and the results show that the impact of ECDZs on urban green innovation resilience is mainly observed in western, inland, and strongly policy-supported regions. The findings of this study provide crucial insights and valuable guidance for developing national environmental conservation policies and programs.